2014
DOI: 10.3109/01443615.2013.874409
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of endometriosis and effects on quality of life: A retrospective study using the short form EHP-5 endometriosis specific questionnaire

Abstract: Complete surgical eradication is considered the mainstay of treatment for endometriosis. The aim of the present study was to investigate patients' own assessment of whether their laparoscopic treatment made a difference to their quality of life, as well as to assess local recurrence rates. We performed a retrospective analysis of 49 women who had laparoscopic treatment for endometriosis at our unit between 1 January 2008 and 1 January 2010. Patients were sent the Short Form EHP-5 questionnaire and asked to sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Indeed, if a treatment results in a difference in QoL, investigators want to be confident that they can detect that difference [18]. The previously discussed study investigated the responsiveness of the English version of the EHP-5 in 40 operated patients [29] and found that mean EHP-5 scores were significantly lower after surgery than before surgery with an important effect size (1.00, from 0.52 to 1.45). It would thus be important to confirm the good responsiveness of the EHP-5 on a broader study with different kind of treatment of endometriosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, if a treatment results in a difference in QoL, investigators want to be confident that they can detect that difference [18]. The previously discussed study investigated the responsiveness of the English version of the EHP-5 in 40 operated patients [29] and found that mean EHP-5 scores were significantly lower after surgery than before surgery with an important effect size (1.00, from 0.52 to 1.45). It would thus be important to confirm the good responsiveness of the EHP-5 on a broader study with different kind of treatment of endometriosis.…”
Section: Discussionmentioning
confidence: 97%
“…We have chosen to analyze the dimensional aspect of the 11 items of EHP-5 together and have found excellent internal consistency; we have thus selected to use the sum of the ratings for all of the items to score the EHP-5. A similar method to score was used in a retrospective study using the short form EHP-5 to evaluate the effects on quality of life of the laparoscopic treatment of endometriosis [29]. Furthermore, both studies demonstrate, as our study, the construct validity of their language version of the questionnaire against different characteristics thought to represent the severity of the related symptoms.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In opposition to separate dimensional aspect evaluation, French EHP-5 version developers have merged all the ratings from core and modular part of questionnaire [20]. A similar scoring method was applied in retrospective study which have estimated impact of laparoscopic treatment of endometriosis on HRQoL [12]. Regardless of implemented scoring method, all abovementioned studies, including ours, have found adequate internal consistency [11,14,20].…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome time impracticality of EHP-30, same group of authors developed Endometriosis Health Pro le-5 (EHP-5) [10]. The EHP-5 questionnaire is proved to be a reliable and valid questionnaire with its special feature in clinical settings where an expeditious endometriosis health status measure is required [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…De Ziegler et al [27] found that using OC 6-8 weeks before assisted reproduction can also increase the pregnancy rate of assisted reproductive technology. Clinical studies have proved that mifepristone is effective in treating EMT-induced infertility [28].…”
Section: Discussionmentioning
confidence: 99%